Association of Helicobacter species with hepatitis C cirrhosis with or without hepatocellular carcinoma. Issue 3 (11th February 2005) - Rocha, M; Avenaud, P; Ménard, A; Le Bail, B; Balabaud, C; Bioulac-Sage, P; de Magalhães Queiroz, D M; Mégraud, F
Abstract : Background and aims: Recent studies have suggested that bacterial coinfection with Helicobacter species in patients already infected with hepatitis C virus (HCV) could be involved in the development of cirrhosis and hepatocellular carcinoma (HCC). A retrospective cross sectional study was performed in order to explore the association between Helicobacter species and HCV associated liver diseases. Methods: The presence of Helicobacter species was tested by polymerase chain reaction on liver samples from four groups of patients. Results: Helicobacter 16S rDNA was found in only 4.2% of liver samples from control patients (n = 24) and in 3.5% of liver samples from patients with non-cirrhotic chronic hepatitis C (n = 29) while it was found in 68.0% of liver samples from patients with HCV positive cirrhosis without HCC (n = 25) as well as in 61.3% of cirrhotic liver samples from patients with HCV positive cirrhosis and HCC (n = 31). In addition, when the HCC tumour tissue was tested (n = 21), 90.5% of samples were positive. DNA from Helicobacter pylori - and Helicobacter pullorum -like organisms was found. Conclusions: There is an association between the presence of Helicobacter species DNA in the liver and hepatitis C cirrhosis, with or without HCC. Indeed, the presence of these bacteria could be the result of structural changes in the liver. Alternatively, Helicobacter species could be a co-risk factor in HCV chronic liver diseases. This result warrants prospective studies to determine the possible causal role of these bacteria in the progression of chronic hepatitis C.